(untitled) (Bangladesh Journal of Agricultural Research, 2015)
A study was carried out to determine the production constraints of modern varieties of potatoes and also find out the probable suggestions to overcome the constraints as verified the views between the farmers and extension officials. Data were collected from 232 farmers sampled randomly from 1547 potato growers and 51 extension officials from 153 population available from the study area of three upazila namely; Durgapur, Mohanpur and Bagmara under Rajshahi district of northwest area of Bangladesh. The study area was selected through multistage sampling procedure with continuous field observation and consultations with teachers, extension personnel, experts and contact farmers along with literatures reviewed. Thus, twenty important constraints regarding potato production were identified and possible suggestions for overcoming the constraints were suggested by using the same procedure. The importance of the constraints and the suggestions were measured by using Important Constraints Score Index (IPSI) and Important Suggestion Index (ISSI). Out of 20 constraints and suggestions views of farmers and officials differed significantly for 15 items and 13 items. Bangladesh J. Agril. Res. 40(1): 95-108, March 2015